EU ETS cap must and can be reduced more quickly - Aleksandar Zaklan; Vicki Duscha; Claudia Gibis; Jakob Wachsmuth; Jan Weiß; Claudia Kemfert (DIW Weekly Report, 2020)
Currently, the European Commission intends to increase the EU's 2030 climate target. Instead of a 40 percent target, greenhouse gas emissions would be reduced by 50 to 55 percent compared to 1990 levels; the European Parliament is even considering a 65-percent reduction. The European Emissions Trading System (EU ETS) sectors should make an appropriate contribution to this reduction. However, decisive for limiting global warming to 1.5 degrees Celsius, as in accordance with the Paris Agreement, is compliance with a consistent emissions budget, the total amount of cumulative greenhouse gas emissions. For the EU ETS, compliance with an emissions budget requires adjusting the emission cap. This Weekly Report derives the minimum requirement for emission reductions in the EU ETS sectors in line with a globally cost-effective emissions budget. The results show the cap must be urgently adjusted to ensure the minimum European contribution to limiting global warming to 1.5 degrees Celsius. Otherwise, beginning in 2030, drastic measures will be necessary to reduce emissions. At the same time, national coal phase-out plans and a more ambitious European energy policy make it possible to approximate the cost-effective pathway by adjusting the cap, without additional reduction requirements for the EU ETS sectors.
Keywords: Q54; Q58; 330; EU ETS; climate policy; Paris Agreement; cap adjustment